Penyuluhan tentang Bahaya Merokok pada Pria di Desa Sorimaon Kec. Batang Angkola Muaratais Kab. Tapanuli Selatan Tahun 2020 - Rahmah Juliani Siregar; Norma Yanti Rambe (Universitas Aufa Royhan Di Kota Padangsidipuan, 2020)
Smoking is a habit of smoking cigarettes that is carried out in everyday life, is a necessity that cannot be avoided for people who experience a tendency towards smoking. Cigarettes are an addictive substance, meaning that they can cause dependence on the wearer. The addictive nature of cigarettes comes from the nicotine they contain. After a person inhales cigarette smoke, within 7 seconds the nicotine will reach the brain (Soetjiningsih, 2010)All health experts including the World Health Organization (WHO) have long concluded that in terms of health, smoking has many negative impacts, especially for children and their future. Cigarettes contain 4000 chemical substances with 200 types of which are carcinogenic (can cause cancer), where this toxic material is found in the main smoke, namely cigarette smoke which is inhaled directly into the smoker's lungs and side smoke, namely cigarette smoke produced by the tip of the cigarette burns, for example carbon monoxide, benzopirene, and ammonia (KPAI, 2013). This PKM activity aims to increase the knowledge of the Sorimanaon Village community about the dangers of smoking by providing education related to efforts to increase knowledge about MKJP. The methods used in the implementation of this activity are through lectures and discussions. The results of this PKM activity aim to increase knowledge by providing good Communication, Information and Education (IEC) with IEC, a communication process will occur with the dissemination of information that accelerates the behavior change of the community.